Analisis Tingkat Keuntungan Usahatani Tanaman Hias di Kelurahan Lubuk Minturun Kota Padang - Dian Fauzi; Ramadhani Ramadhani; Syahrial Syahrial (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
This study aims to analyze the profit level of ornamental plant farmers in Lubuk Minturun Village, Padang City. The method used is farming analysis with a sampling technique that is Proportional Random Sampling with the number of samples taken by as many as 30 respondents. Data analysis techniques used are cost analysis, revenue analysis, profit analysis, and R/C analysis. Based on the results of farming analysis, the average profit obtained by ornamental plant farmers in Lubuk Minturun Village is Rp.4.195.926.81/year/farmer with an R/C of 1.21.